Characteristics of antidepressant medication users in a cohort of mid-age and older Australians. (March 2015) - Paige, Ellie; Korda, Rosemary J; Kemp, Anna; Rodgers, Bryan; Banks, Emily
Objectives: We aimed to investigate antidepressant use, including the class of antidepressant, in mid-age and older Australians according to sociodemographic, lifestyle and physical and mental health-related factors. Methods: Baseline questionnaire data on 111, 705 concession card holders aged ⩾45 years from the 45 and Up Study —a population-based cohort study from New South Wales, Australia—were linked to administrative pharmaceutical data. Current- and any-antidepressant users were those dispensed medications with Anatomical Therapeutic Chemical classification codes beginning N06A, within ⩽6 months and ⩽19 months before baseline, respectively; non-users had no antidepressants dispensed ⩽19 months before baseline. Multinomial logistic regression was used to calculate adjusted relative risk ratios (aRRRs) for predominantly self-reported factors in relation to antidepressant use. Results: Some 19% of the study population (15% of males and 23% of females) were dispensed at least one antidepressant during the study period; 40% of participants used selective serotonin reuptake inhibitors (SSRIs) only and 32% used tricyclic antidepressants (TCAs) only. Current antidepressant use was markedly higher in those reporting: severe versus no physical impairment (aRRR 3.86(95%CI 3.67–4.06)); fair/poor versus excellent/very good self-rated health (4.04(3.83–4.25)); high/very high versus low psychological distress (7.22(6.81–7.66)); ever- versus never-diagnosis of depression by a doctor (18.85(17.95–19.79)); low-dose antipsychotic use versus no antipsychotic use (12.26(9.85–15.27)); and dispensing of ⩾10 versus <5 other medications (5.97(5.62–6.34)). Sociodemographic and lifestyle factors were also associated with use, although to a lesser extent. Females, older people, those with lower education and those with poorer health were more likely to be current antidepressant users than non-users and were also more likely to use TCAs-only versus SSRIs-only. Conclusions: Use of antidepressants is substantially higher in those with physical ill-health and in those reporting a range of adverse mental health measures. In addition, sociodemographic factors, including sex, age and education were also associated with antidepressant use and the class of antidepressant used.